The Feasibility of Floating, Production, Storage and Offloading (FPSO) Vessel in Marginal Field - ,, Nurul Arifarhana (Universiti Teknologi PETRONAS, 2021)
FPSO is a common vessel currently in service in offshore industry. In the economic aspect, it is said that fixed structures such as steel jackets or concrete platforms are not practical where pipelines must be built in the seabed, and expensive, particularly for marginal fields. For successful use of FPSO in marginal field, analysis on the dynamic responses due to environmental forces is needed. Dimension of FPSO from the Berantai is adopted while the environmental data requirements for operating condition of wave height, period, wind and current speed are based on the Petronas Technical Standards (PTS) is used in this study. The FPSO is modelled conservatively based on a 2-D structure with three degrees of motion which are surge, heave and pitch. The wave forces of the FPSO are calculated using the Froude-Krylov Principle. This theory uses the method for determining the forces of incident wave pressure and pressure area on a larger surface.